2020
DOI: 10.4314/ajesms.v16i.2.7
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Practical Work in Physics on Academic Performance among Learners at the selected secondary school in Rwanda

Abstract: The current study investigates the effectiveness of practical work in physics on academic performance among learners of a secondary school in Rwanda. The study employs a quasi-experimental research design specifically pretest-posttest control group design (control group and experimental group). Two groups of learners of senior one at Groupe Scholaire Rugoma were treated differently through an expository and practice-based approach respectively. Physics achievement test prepared to evaluate the effect of practi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Nowadays, the forerunner of teaching and learning science concepts is practice-based education. Studies have shown that this mode of instructional delivery equips students with practical skills through learning by doing, which promotes their knowledge, skill acquisition and performance [1], [2]. As such, Ministry of Education included practical work to Ghana's senior high school biology curriculum.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Nowadays, the forerunner of teaching and learning science concepts is practice-based education. Studies have shown that this mode of instructional delivery equips students with practical skills through learning by doing, which promotes their knowledge, skill acquisition and performance [1], [2]. As such, Ministry of Education included practical work to Ghana's senior high school biology curriculum.…”
Section: Introductionmentioning
confidence: 99%
“…The preliminary observations by the researchers and WAEC reports suggest a significant gap between the ideal conditions required for effective practical work and the current practices in the school. The observed challenges point to deficiencies in the implementation of practical work sessions, where students may not be adequately guided through these crucial components of the curriculum [1], [6], [7]. The urgency of addressing this issue lies in the increasing number of students performing inadequately in biology.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations